2020
DOI: 10.1155/2020/1701843
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Unsteady Characteristics and the Impact Performance of a High-Pressure Submerged Cavitation Jet

Abstract: High-pressure submerged cavitation jet is widely used in the fields of material peening, petroleum drilling, and ocean engineering. The impact performance of the jet with intensive cavitation is related to the factors such as working condition and the nozzle geometry. To reveal the relationship between the nozzle divergent angle and the jet pressure on the unsteady characteristics of the jet, high-speed photography with frame rate of 20000 fps is used to record the image of the cavitation clouds. Grayscale ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…After an impingement by a cavitation water jet, the surface properties of materials can be improved to a certain extent, and a certain thickness of strengthening layer will be formed on the surface of the materials. The existence of a residual compressive stress field near the surface of a material can balance the tensile stress generated on the surface of that material during the stressing process, as well as inhibit the initiation of cracks on the surface and subsurface of the material, reduce the expansion speed of cracks and, finally, improve fatigue life [12,13]. Soyama et al first investigated the cavitation water jet in terms of improving the surface performance of parts and components and found that the residual compressive stress on the surface of parts and components after a cavitation water jet treatment has been significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…After an impingement by a cavitation water jet, the surface properties of materials can be improved to a certain extent, and a certain thickness of strengthening layer will be formed on the surface of the materials. The existence of a residual compressive stress field near the surface of a material can balance the tensile stress generated on the surface of that material during the stressing process, as well as inhibit the initiation of cracks on the surface and subsurface of the material, reduce the expansion speed of cracks and, finally, improve fatigue life [12,13]. Soyama et al first investigated the cavitation water jet in terms of improving the surface performance of parts and components and found that the residual compressive stress on the surface of parts and components after a cavitation water jet treatment has been significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…In order to master the flow characteristics of cavitation jet and the impact mechanism during cavitation formation and collapse, and improve the impact effect of a high-pressure cavitation jet, many researchers have studied the velocity field, pressure distribution and cavitation shape of a cavitation jet. Yang Y et al [12][13][14] captured the unsteady flow characteristics of a high-pressure cavitation jet at three different angles through high-speed photography experiments, and extracted its growth, shedding and collapse information from high-speed images. Ryuta Watanabe et al [15,16] applied the POD image processing technology to the high-speed image analysis of a cavitation jet, and analyzed the position of the cavitation bubble collapse through an algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…e pulsed jet can reduce the pressure holding effect of bottom-hole rock, improve the stress state of rock, and enhance the effect of rock breaking and rock cleaning [8]. Both the abrasive water jet and pulsed water jet have distinctive characteristics [9][10][11][12][13][14][15], using some appropriate modulation methods can integrate their rockbreaking advantages and get a much better effect than using any of them alone.…”
Section: Introductionmentioning
confidence: 99%